2004
DOI: 10.1021/la0400306
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Membrane Formation by Vesicle Fusion on Silicon Dioxide Surfaces Modified with Alkyl Self-Assembled Monolayer Islands

Abstract: Using atomic force microscopy, we have investigated the formation of the dipalmitoylphosphatidylcholine (DPPC) membrane by the vesicle fusion method on SiO2 surfaces modified with self-assembled monolayer (SAM) islands of octadecyltrichlorosilane (OTS) with sizes comparable to those of the vesicles. OTS-SAM islands with various sizes and coverages can be constructed on the SiO2 surfaces prepared by thermal oxidation followed by partial hydroxylation in a H2O2/H2SO4 solution. When vesicles are sufficiently smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…The interaction between lipid bilayer membranes and solid substrates is a quite influential factor during the vesicle fusion processes shown in Figure 1, as well as other factors, like the lipid components [56,57] and the size of vesicles [58,59,60,61,62], the solute concentration in the solution [40,58] and temperature. At the early stage of SLB researches, adsorption states of vesicles and transformation processes to a planar membrane was characterized in situ with label-free methods, such as quartz crystal microbalance [63], ellipsometry [64,65], surface plasmon resonance [64] and AFM [66].…”
Section: Substrate Effects On Slb Formation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between lipid bilayer membranes and solid substrates is a quite influential factor during the vesicle fusion processes shown in Figure 1, as well as other factors, like the lipid components [56,57] and the size of vesicles [58,59,60,61,62], the solute concentration in the solution [40,58] and temperature. At the early stage of SLB researches, adsorption states of vesicles and transformation processes to a planar membrane was characterized in situ with label-free methods, such as quartz crystal microbalance [63], ellipsometry [64,65], surface plasmon resonance [64] and AFM [66].…”
Section: Substrate Effects On Slb Formation Processmentioning
confidence: 99%
“…The transformation processes from vesicles to a SLB are strongly affected by the physical and chemical properties of the substrate surfaces, such as materials [40,59,60,63,67,82,83,84,85,86], chemical termination [25,26,62,63,87,88,89] and surface charges [54,90,91]. As a comprehensive parameter including several surface properties, the hydrophilicity of surfaces is useful to express the behavior of the vesicles on the surfaces.…”
Section: Substrate Effects On Slb Formation Processmentioning
confidence: 99%
“…Vesicle suspensions were prepared through the following procedure [10] of TR-DPPE was evaporated onto the wall of a glass vial by bowing N 2 gas, and evacuated overnight; Secondly, the lipid mixtures were re-suspended in buffer solutions (10 mM HEPES, 150 mM KCl, pH 7.4 (NaOH)) with various CaCl 2 concentrations (0.001, 0.1, 1 100 mM) by vortexing moderately to prepare vesicle suspension with the total lipid concentration of 100 ÎŒM; Finally, the vesicle suspensions were agitated and sonicated, and they were fractured applying freeze-and-thaw cycles in liquid nitrogen three times, and extruded through a 100 nm polycarbonate filter 19 times at 45 °C. The sample was not exposed to the air during preparation.…”
Section: Vesicle Preparation and Formation Of Slbmentioning
confidence: 99%
“…Typically, bilayers have been stabilized on oxidized silicon surfaces or polymers. [19][20][21][22][23][24][25][26] Stabilization of monolayers has always been a little bit more of a challenge. Successful studies are reported; however, the stabilization has always involved the formation of covalent bonding between the acryloyl-phospholipids and an intermediate acrylate modified silicon oxide surface or acrylated polymer.…”
Section: Introductionmentioning
confidence: 99%